A flow analysis of hybrid nanoparticles near a solid sphere. (30th April 2022) - Salahuddin, T.; Khan, Mair; Sakinder, S.; Al Alwan, Basem
Abstract: In this article, the physical impact on thermal performance of unsteady incompressible hybrid nanofluid C u − G O / ( H 2 O ) − C 2 H 6 O 2 (50:50 vol%) has been presented by using the implicit finite difference procedure. A rigid circular object is taken for instance at time t = 0, a free stream flow hits the outer surface of the circular object. The fluid crosses the boundary of the circular object at different positions. A highly non-linear complex partial differential system is achieved which is solved numerically. The infiltration of various parameters for instance: nanoparticle shapes (cylinders, bricks and Platelets) and volume fraction parameters on velocity profile, skin friction, temperature profile and Nusselt number are demonstrated qualitatively through illustrations. Outputs specify that: mono nanofluid and hybrid nanofluid created by extending volume fractions causes diminution in the velocity profile. Furthermore, solid hydrogen bonding of hybrid nanofluid reasons a sharp growth in thermal conductivity and, thus, rise in temperature profile is noticed. Moreover, the heat transfer rate and temperature profile has always been influenced by different shape factor, so the cylindrical shape particles lead this category afterwards, bricks and platelets. It is noticed that rise in volume fraction parameters show reduction in velocity profile, but opposite impact is noticed in temperature distribution. Moreover, the thermal performance of hybrid nanoparticles is better than the mono nanoparticles. Highlights: GO- Cu/H2O– C2H6O2 (50:50 vol%) hybrid nanofluid has been presented. A rigid circular object is taken. The different shapes of nanoparticles has been considered. The fluid crosses the boundaries of the circular object at different positions. A highly non-linear complex partial differential system is achieved which is solved numerically.